User-Centered Development of a Trustworthy E-Voting Application for Student Elections - Jefri Marzal; Suwannit Chareen Chit; A. Zarkasi; Niken Rarasati (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2026)
Developing a secure and reliable remote electronic voting (e-voting) application presents critical challenges, particularly in ensuring system integrity, security, and user trust. This study focuses on designing and evaluating an e-voting system for student leader elections, with the objective of addressing the key factors that influence voter confidence. The development process followed structured phases: analysis, design, development, implementation, and evaluation. Key concerns, such as transparency, voter anonymity, prevention of duplicate voting (singularity), and result integrity, were addressed. A survey was conducted with 1,000 randomly selected students to assess their primary concerns and level of trust in the system. Results indicate that transparency, singularity, integrity, and anonymity are the most crucial requirements for an e-voting system. To enhance trust, efforts were made from the design phase through socialization, including educational campaigns, application demonstrations, and user training. Rigorous testing was conducted by internal developers and external stakeholders, followed by a public trial. Out of 3,527 survey respondents, 68.04% expressed trust in the application, deeming it “feasible” for adoption. However, areas such as transparency and feedback mechanisms require further improvement to fully address user concerns. This study contributes to the e-voting field by underscoring the importance of user involvement and extensive testing in developing a trustworthy system for student elections.